A Rare Case of Undescended Caecum Accompanied by Looped Retroperitoneal Appendix. - Ashwini AP,; Naveen K,; Jyothsna P,; Swamy RS,; Satheesha NB, (Department of Surgery, UKM Medical Centre, 2014)
Intestinal malrotations are associated with various anatomical anomalies. We report a unique case wherein the caecum was located in the right lumbar region instead of the right iliac fossa. The ileo-caecal junction was also placed higher up. The appendix was ‘uncinate’ shaped, highly coiled and retroperitoneal with the absence of meso-appendix. Both, the caecum and appendix were supplied by ascending branch of the ileocolic artery instead of the descending branch. Further, we also observed that the ascending colon was very short and sub-hepatic in position. Such type of variations is of clinical and surgical importance in diagnosis and treatment of appendicitis.